Effect of salt stress on plant growth and metabolism of bean plant Vicia faba (L.) - Amira M.S. Abdul Qados (Journal of the Saudi Society of Agricultural Sciences)
The effect of sodium chloride (NaCl) concentrations (0.0, 60, 120, 240 mM) on growth, osmotic potential, chlorophyll content, protein content of (Vicia faba L.) seedlings was investigated. NaCl caused an increase in plant height with low and medium concentrations and a decrease with the highest concentration, in both measurement periods. No significant effect was observed in the number of leaves or leaf area with low concentration, while a decrease was noticed for each, with two higher concentrations and in both measurement periods. Salinity increased both fresh and dry weights of the shoot in the two measurement periods. Osmotic potential (O.P.) showed a significant decrease with the increase in concentrations, and in the duration of the stress periods. Salinity significantly reduced chlorophyll ‘a’ content in both measurement periods. It also significantly reduced chlorophyll ‘b’, total chl., and carotenoids contents after ten days of treatment. An increase was observed in the protein content in the two measurement periods due to the impact of salinity stress. A directly proportional relationship was found between protein content and the increase in salt concentrations in the first measurement period, while it was inversely proportional in the second.